2023
DOI: 10.3390/ijms24043432
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Quenching Autofluorescence in Fixed Mouse Adrenal Cortex Tissue

Abstract: Tissue autofluorescence of fixed tissue sections is a major concern of fluorescence microscopy. The adrenal cortex emits intense intrinsic fluorescence that interferes with signals from fluorescent labels, resulting in poor-quality images and complicating data analysis. We used confocal scanning laser microscopy imaging and lambda scanning to characterize the mouse adrenal cortex autofluorescence. We evaluated the efficacy of tissue treatment methods in reducing the intensity of the observed autofluorescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This indicated that RL/C 60 could be detained in colonic tissue for a long time, favoring the delivery of C 60 in inflammation sites. Meanwhile, only tissue autofluorescence 46 was observed in brain, kidney, spleen, heart and lung (the only exception came from UC mice liver 6 h after RL/C 60 dose), proving no massive cumulation of RL/C 60 in main organs other than colon.…”
Section: Resultsmentioning
confidence: 95%
“…This indicated that RL/C 60 could be detained in colonic tissue for a long time, favoring the delivery of C 60 in inflammation sites. Meanwhile, only tissue autofluorescence 46 was observed in brain, kidney, spleen, heart and lung (the only exception came from UC mice liver 6 h after RL/C 60 dose), proving no massive cumulation of RL/C 60 in main organs other than colon.…”
Section: Resultsmentioning
confidence: 95%
“…The adrenal gland is widely known to be autofluorescent, which is attributed to its high lipid content 36 . To ensure that the autofluorescent macrophages were not an artefact of fluorescent imaging, we characterised the autofluorescent signature of the aged (20-week-old) adrenal gland, finding wide spectral autofluorescent signals which decline as we approach the far-red end of the light spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that samples should be regularly checked to prevent sections from drying out during SBB and TrueBlack ® treatments. Although TrueVIEW ® has been used to suppress AF in various formaldehyde-fixed tissues such as spleen, pancreas, aorta, liver, skin, and lung, 28 , 29 its efficiency was found to be lower than SBB and TrueBlack ® , making it a suboptimal choice for AF quenching in myocardial samples.…”
Section: Discussionmentioning
confidence: 99%